Implementing qur’anic environmental education values through a community-based household waste management program - Akhmad Zaenul Ibad; Oni Marliana Susianti; Srifariyati Srifariyati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study addresses the growing problem of household waste in Pemalang Regency, Indonesia, where waste management practices remain largely technical and insufficiently value-oriented. Drawing on Qur’anic teachings that emphasize human responsibility as khalifah (stewards of the earth), this study aims to examine the implementation of Qur’an-based environmental education through a community-based household waste management mentoring program. Using a qualitative approach with the Participatory Action Research (PAR) method, the study involved 100 community members, six facilitators, and local religious and community leaders. Data were collected through participant observation, in-depth interviews, documentation, and semi-structured questionnaires as supporting instruments. Data analysis followed the interactive model of Miles and Huberman, supported by triangulation to ensure credibility. The findings indicate that the internalization of Qur’anic values such as khalifah, amanah, mizan, and the prohibition of fasad contributed to increased ecological awareness and behavioral change in household waste management practices, including waste segregation, reduction, and recycling. The mentoring process also fostered collective participation and strengthened community-based ecological responsibility. This study concludes that Qur’an-based environmental education implemented through a participatory mentoring approach can effectively promote sustainable household waste management while reinforcing the integration of Islamic spiritual values into community-driven environmental practices.